The Classification of the Suras (Part Two): Organization According to the Rule of Thirds and Sura Al-Furqān - Relationship with Suras Al-Fātiḥah and Fuṣṣilat - BENZITOUNI, Saadane (Journal of Quranic Sciences and Research, 2026)
This study highlights the existence of a simple organizing principle based on the proportion of one-third (1/3). This principle acts as a structural law governing the numerical architecture of the Quran. It manifests itself in two independent yet formally comparable domains. In both cases, the proportion is verified through strict structural equalities, albeit of fundamentally distinct natures. In the ordinal domain, it is an equality of compensation between the sums of negative and positive ranking values. In the versetic domain, it is an equality between the sums of verses of the long and short suras as determined relative to a threshold. The application of this proportion to the longest sura (286 verses) defines an objective threshold Vs=⌊286/3⌋≈95. Partitioning the corpus according to this threshold reveals a difference of 154 verses between the totals of the two groups. The analysis shows that this difference is resolved only by the functional intervention of a single sura: Al-Furqān (No. 25). Its number of verses (77) corresponds exactly to half of the gap, and its logical transfer restores a perfect equality (3 118 verses). The subset (Fq) obtained after the application of the one-third proportion satisfies a Type 1 equation, thereby demonstrating its autosimilarity. In the ordinal domain, the same proportion (114/3 = 38) generates a hierarchical 1:2 partition whose coherence also relies on strict equalities and autosimilar properties. The coexistence of a unique proportional principle, strict equality conditions, and autosimilar structures locked by entire equations suggests a highly constrained mathematical architecture of the Noble Qur’an.